Accounting practices in the oil and gas industry in Malaysia - Naiimi, Nazirah; Mohd Rodzi, Nor Kartini; Mohd Noor, Marjan (Faculty of Accountancy, 2024)
The oil and gas exploration and production sector plays an important role in the global economy as one of the world's primary fuel sources. For example, investments in oil and gas reached more than US$511 billion in 2020 (Fuller, 2024). Financial reporting in the oil and gas sector is challenging because of complex operations, varied accounting practices, and the need to accurately represent exploration, production, and distribution activities (Gray et al., 2019). In the complex and dynamic oil and gas industry, accountants specializing in oil and gas accounting cultivate advanced skills in financial reporting analysis, forecasting, and risk assessment capabilities highly valued by employers globally. Moreover, expertise in this niche area offers a distinct competitive advantage in the job market, where the demand for professionals with specialized knowledge in oil and gas accounting remains consistently high (Vyde, n.d.).